Influence of levamisole and Freund's adjuvant on mouse immunisation with antigens of adults of the liver fluke Fasciola hepatica Linnaeus, 1758 - Gutierrez-Sanchez, Maria de Los Angeles; Luna-Herrera, Julieta; Trejo-Castro, Lauro; Montenegro-Cristino, Natividad; Almanza-Gonzalez, Alfredo; Escobar-Gutierrez, Alejandro; de la Rosa-Arana, Jorge Luis (Folia parasitologica, 2015)
We have studied the influence of both levamisole (AL) and Freund's adjuvant (AF) on the immunisation of mice with the secretory antigens of adults of the liver fluke Fasciola hepatica Linnaeus, 1758. Total IgG antibodies were detected in all groups where the F. hepatica antigen was administered, been levels of IgG1 increased respect to IgG2a antibodies. During immunisation, IL-4 and IFN-γ were only detected in AL and AF groups, but after infection, IL-4 boosted in all groups. IFN-γ increased two fold in AF and AL groups compared to the saline solution (AS) group. Worm recovering was of 32-35% in groups administered without antigen whereas in AS, AL and AF groups recovering was of 25%, 12% and 8%, respectively. Macroscopical lesions in the liver were scarce in AL and AF groups. Our data suggest that immunisation of mice with antigens of F. hepatica enhances the immune response avoiding both liver damage and worm establishment after challenge infection. The murine model of fasciolosis has appeared to be useful to elucidate the mechanism by which the parasite modulates immune responses toward a Th2 type but also the development of Th1 type-inducing vaccines.
Keywords: Lymnaea; Antigens, Helminth; metacerkárie; Freund's Adjuvant; velikost orgánu; Parasite Load; parazitární zátěž; Fascioliasis; Kinetics; Statistics as Topic; kinetika; Mice; imunomodulace; tělesná hmotnost; modely u zvířat; statistika jako téma; Body Weight; Freundovo adjuvans; Levamisole; Models, Animal; Fasciola hepatica; fasciolóza; antigeny helmintové; Metacercariae; levamisol; játra; In Vitro Techniques; Immunomodulation; techniky in vitro; Organ Size; Liver; myši